2013
DOI: 10.1016/j.neuint.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and oxidative stress: Co-conspirators in the pathology of Parkinson’s disease

Abstract: Parkinson's disease (PD) is a complex disease, with genetics and environment contributing to the disease onset. Recent studies of causative PD genes have confirmed the involvement of cellular mechanisms engaged in mitochondrial and UPS dysfunction, oxidative stress and apoptosis in the progressive degeneration of the dopaminergic neurons in PD. In addition, clinical, epidemiological and experimental evidence has implicated neuroinflammation in the disease progression. This review will discuss neuroinflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
173
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(181 citation statements)
references
References 250 publications
(190 reference statements)
3
173
0
5
Order By: Relevance
“…In particular, the complex I inhibitory effects of rotenone have been tied to the onset of a parkinsonian phenotype in both animal models and human studies (2-4). Although much focus has been placed on oxida- tive stress and the role it may play in the pathogenesis of neurodegeneration in PD (9,(32)(33)(34), there is substantial evidence to suggest that mitochondrial dysfunction may also contribute to this process (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the complex I inhibitory effects of rotenone have been tied to the onset of a parkinsonian phenotype in both animal models and human studies (2-4). Although much focus has been placed on oxida- tive stress and the role it may play in the pathogenesis of neurodegeneration in PD (9,(32)(33)(34), there is substantial evidence to suggest that mitochondrial dysfunction may also contribute to this process (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…A link between inflammation and PD was first described in a postmortem study by McGeer et al in 1988, where activated microglia was found in the SN of PD patients [34]. Furthermore, several clinical studies have confirmed this association by reporting increased microglial activation and elevated pro-inflammatory cytokines in post-mortem brains and CSF [35][36][37] (Figure 2). These data have been also reproduced by experimental studies in animal models of the disease [23,38,39], where neuroinflammation has been shown to be an important contributor to PD progression.…”
Section: Introductionmentioning
confidence: 71%
“…In postmortem brains from PD victims markers of lipid peroxidation are found 6 . Malodyaldhyde (MDA) is a specific marker of lipid peroxidation, which is largely a result of the peroxidation of polyunsaturated fatty acids with more than two double bonds 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanisms proposed to explain the events culminating in neuronal death in PD are associated with mitochondrial changes, apoptosis and elevated levels of oxidative stress 5 . There is also a neuroinflammatory process with activation of glial cells and release of cytokines and nitric oxide 6 . Therefore, the process of degeneration is multifactorial.…”
mentioning
confidence: 99%